2019
DOI: 10.1016/j.foodchem.2018.09.146
|View full text |Cite
|
Sign up to set email alerts
|

Chayote (Sechium edule): A review of nutritional composition, bioactivities and potential applications

Abstract: Chayote (Sechium edule) has gained widespread consuming acceptance and recognized by its nutritional and bio-functional properties. The present review surveys and describes the current findings about the nutritional, phytochemical and pharmacological properties of chayote and identifies opportunities for further research. It also discusses chayote's versatile utility in nutrition, as a functional ingredient in food, cosmetic and pharmaceutical industries, as well as in nanotechnology and biotechnological proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 61 publications
(87 reference statements)
2
50
1
2
Order By: Relevance
“…This explains the wide use of Sechium edule (S. edule) with curative purposes in México and worldwide. Likewise, in some studies it has been reported to have antioxidant, anti-inflammatory, hypoglycemic, hypotensive as well as lipogenesis inhibition properties [18,19]. It could therefore be an alternative treatment for the control of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…This explains the wide use of Sechium edule (S. edule) with curative purposes in México and worldwide. Likewise, in some studies it has been reported to have antioxidant, anti-inflammatory, hypoglycemic, hypotensive as well as lipogenesis inhibition properties [18,19]. It could therefore be an alternative treatment for the control of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Current research reported that beluntas, papaya leaves, katuk (Sauropus androgynus), and kelor (M. citrifolia) contain high antioxidant and bioactive compounds (Barba et al 2014;Andarwulan et al 2012;Otsuki et al 2010). Chayote leaves prominently have antihypertensive properties and anti-diabetic properties (Vieira et al 2019). M. citrifolia leaf ethanol proved has larvicidal and pupicidal activities (Lopes et al 2018).…”
Section: Plant-based Proteinmentioning
confidence: 99%
“…The genetic erosion of chayote is boosted through the inbreeding and usage of cloned plants in orchids increasing the incidence of viruses and fungal plants infected [101]. The chayote holds high nutritional value with high antioxidant activity, rich in important amino acids (particularly: arginine, aspartic acid, leucine, proline among others), recently it has been pharmacologically analyzed for antimicrobial, anti-inflammatory, cardiotonic, cytotoxic and antitumor action [37]- [41]. In order to take advantage of nutritional and pharmacological properties cytogenetic analyses are proposed.…”
Section: Sechiumedule a Prominent Nucusmentioning
confidence: 99%